Systematic Literatur Review (SLR) : Faktor Penyebab Kegagalan Pengembangan SDM di Perusahaan - Abdul Rhosid; Ariyandi Quliyawan; Partini Partini; Qulud Dwitika Kusuma; Sri Hartono (Universitas Muhammadiyah Ponorogo, 2025)
This study aims to analyze the factors that cause human resource development (HRD) failure in companies through the systematic literature review (SLR) method with the PICO approach. This study highlights that failure in HR development is often caused by lack of management commitment, limited resources, irrelevant training strategies, and resistance to change. In addition, organizational culture that does not support learning is also a major obstacle. Herzberg's motivation theory and Lewin's theory of change are used as the basis for analysis, while the 70-20-10 model provides a modern perspective on experiential learning. The findings show that while HR development requires management commitment and organizational culture support, systematic evaluation remains a key element to ensure the success of training programs. The research also provides strategic recommendations, including increased budget allocation, better management of change, and alignment of training strategies with specific business needs. The results of this study are relevant to address the challenges of modern businesses in improving competitiveness through effective HR development.